ELUSIDASI STRUKTUR ISOLAT SKUALENA DARI IKAN HIU CUCUT BOTOL (Centrophorus sp) - Aniek Setiya Budiatin (The East Java Biological Society, 2005)
The main source of squalene was liver oil of shark. Producing of squalene this oil could be separated from other components inside. The research obtained that the value of squalene was 75.83 ± 1.14%. To discover the purification and safety to consume squalene which had been isolated from oil of the liver’s shark cucut botol ‘ was used a method which available in AOAC, therefore that could be done elucidation of the structure of isolate with any instruments such as KLT; FTIR; GC; GC-MS; and NMR. Structure elucidation of isolate compare with standard of squalene had result as follows: a. KLT: Rf isolate = 0.457; Rf standard = 0,457; b. FTIR = 2980– 2850 CH of methyl and methylene; 1668.58 & 1446.74 a double chain of carbon (C=C); 1381.16 & 835.25 = branch chain that all for isolate was the same with standard; GC tR = 9.065 minute of isolate and standard was 9.124 minutes; GC-MS the main fraction with mass 69 was one unit of isoprene (C5H9); the value of proton NMR (δ = ppm) were 1.601 & 1.674; 2.016; 5.150 & 5.155 for isolate; the standard were 1.599 & 1.670; 2.016; 5.155. The result of elucidation structure could be concluded that the isolate was the same with the squalene standard. Therefore, isolate could be able to consume safety as natural health food for all consumers because it had already pure and free from other compound such as cholesterol.